Attitude towards learning school geometry: an exploratory and confirmatory factor analysis in the Nigerian context - Muhammad Nasiru Hassan; Muhammad Ammar Naufal; Abdul Halim Abdullah (Intelektual Pustaka Media Utama, 2026)
Attitude is a critical factor influencing students’ success in learning geometry and mathematics, which has been a subject of global interest in educational research. This study aimed to develop a valid and reliable instrument to measure students’ attitudes toward learning geometry in Nigeria, based on the affective, behavioral, and cognitive (ABC) model. The instrument was tested on a sample of 100 secondary school students in Nigeria. To ensure its validity, both exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were employed. The EFA results indicated a three-factor structure consisting of 20 items, which was further verified through CFA, showing good model fit indices and supporting the instrument’s robustness. The reliability of the instrument was also confirmed, with Cronbach’s alpha coefficients ranging from 0.73 to 0.89, suggesting strong internal consistency across the three attitude components. The findings indicate that the developed instrument is a reliable and valid tool for assessing secondary school students’ attitudes toward geometry, capturing their emotional, behavioral, and cognitive responses to the subject. This study contributes significantly to the field of mathematics education by offering a context-specific tool for measuring attitudes, which could inform the development of more effective teaching strategies tailored to students’ attitudes toward geometry.